A Controlled Study of Suicide in Middle‐Aged and Older People: Personality Traits, Age, and Psychiatric Disorders. Issue 2 (17th August 2013) - Draper, Brian; Kõlves, Kairi; De, Diego; Snowdon, John
<x xml:space="preserve">Abstract</x> Personality traits were examined using the NEO Five‐Factor Inventory–Revised in an Australian psychological autopsy study involving 259 suicide deaths and 181 sudden death controls aged 35 years and over. Interviews included the Structured Clinical Interview for DSM‐IV to determine the presence of psychiatric disorder. Personality traits of suicide deaths differed significantly from those of controls, scoring higher in the Neuroticism and Openness to Experience domains and lower on the Agreeableness and Extraversion domains. These findings varied with the presence of psychiatric disorder and by age. High Neuroticism scores were the most consistent finding in people who died by suicide, although these scores decreased in older suicides.